Pendampingan Pengisian E-SPT Tahunan Wajib Pajak Orang Pribadi Pada PT. BPR Bantoru Perintis - Lenny Panggabean; jisman m lubis; Beatrix Delfina; Nasib Pola Manurung; Daniel Kopong; Daniel Owen (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
The reluctance of taxpayers to submit annual e-SPT reports stems from the stigma of public distrust of tax officials; very complicated tax regulations that are difficult for taxpayers to understand; a large number of tax regulations issued every year; and a lack of socialization against tax regulations. A questionnaire filled out by twenty-five employees of PT. BPR Bantoru Perintis. Respondents who filled out the questionnaire were mostly male, with the most common age range being 25 to 30 years, having the highest annual income ranging from IDR 60,000,000 to IDR 250,000,000, having a high school education level, and having attended counseling or tax socialization. If multiple linear regressions are carried out with the help of the SPSS program on questions regarding the impact of tax awareness and tax sanctions on compliance with payment and reporting of individual annual tax returns, it can be said that awareness of taxes and tax sanctions significantly and simultaneously affect compliance with payment and reporting of annual tax returns. In addition, compliance with payment and reporting of individual annual tax returns will be affected by 50.9% of awareness of taxes and tax sanctions, while the remaining 49.1% are influenced by other variables.